ARTIFICIAL INTELLIGENCE AS A TOOL FOR CHANGING THE FUTURE OF MEDICINE: A COMPREHENSIVE REVIEW (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Artificial intelligence (AI) is revolutionizing medicine by enhancing diagnostics, enabling personalized treatments, and optimizing healthcare delivery. This review explores the transformative potential of AI in medicine, drawing on 18 studies from diverse global authors and institutions. We examine applications in medical imaging, drug discovery, personalized medicine, and healthcare management, while addressing challenges such as data quality, ethical considerations, and integration into clinical practice. The findings highlight the need for interdisciplinary collaboration, robust regulatory frameworks, and continuous innovation to fully realize AI's potential in shaping the future of medicine.